Sustainability : a systems engineering approach to the global grand challenge - Badiru, Adedeji Bodunde, 1952-; Agustiady, Tina (Analytics and control, 2021)
"Sustainability is one of the most embraced topics nowadays. Everybody is affected by issues of sustainability. Every organization needs to pay attention to these issues. As long as more people and more organizations are engaging in business and industry activities, there will always be a need for sustainability. This book presents tools such as lean six sigma to help sustain results by using process focused decisions. This book covers tools and techniques of industrial engineering to promote sustainability. It discusses a systems approach, the evolution of new products, development of sustainability alliances, and highlights the role of sustainability in advancing organizational goals. The book also addresses sustainability as a coordinated project using a project management approach. It includes the interface of humans and technology and presents an integration of analytics. The book is ideal for all engineering, business, and management fields"--